The number of discernible colors in natural scenes - Linhares, João M. M. (2008)
The number of colors discernible by normal trichromats has been estimated for the idealized object-color solid. How well these estimates apply to natural scenes is an open question, as it is unknown how much their colors approach the theoretical limits. The aim of this work was to estimate the number of discernible colors based on a database of hyperspectral images of 50 natural scenes. The color volume of each scene was computed in the CIELAB color space and was analyzed using the CIEDE2000 color-difference formula. It was found that the color volume of the set of natural scenes was about 30% of the theoretical maximum for the full object-color solid, and it corresponded to a number of about 2.3 million discernible colors. Moreover, when the lightness dimension was ignored, only about 26,000 (1%) could be perceived as different colors. These results suggest that natural stimuli may be more constrained than expected from the analysis of the theoretical limits. © 2008 Optical Society of America.